Contract farming- a safer option? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
For subsistence farmers who want to start growing cash crops, the danger that they will not find a good market may be a strong disincentive. Contract farming may be one solution, as it guarantees that farmers will have a market. This report from Tanzania features a company that makes contracts with farmers to cultivate flower seeds for export to Holland.